MATHEMATICAL PROBLEM SOLVING ABILITY IN VIEW OF LEARNING STYLES - Muhammad Arie Firmansyah; Lely Laillatus Syarifah (Prima: Jurnal Pendidikan Matematika, 2023)
Problem solving ability is very important in mathematics education, because problem solving ability is one of the goals in learning mathematics. The ability to solve mathematical problems is influenced by various factors, including the various student learning styles. This study aims to describe students' mathematical problem solving abilities in terms of learning styles. This research uses a qualitative descriptive approach. The subjects used were 8 semester 1 students, 6 students were taken with the following details, namely 2 students with a visual learning style, 2 students with an audiotorial learning style, and 2 students with a kinesthetic learning style. Data collection techniques used learning style questionnaires, problem solving ability tests, and interviews. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of this study show a description of students' mathematical problem-solving abilities in terms of learning styles as follows: (1) visual students can understand the problem well, devise an appropriate solution plan, carry out the plan correctly, and re-check the answers that have been made. (2) auditory students can understand the problem well, develop appropriate resolution plans, carry out plans correctly, but do not carry out the stage of re-checking answers. (3) auditory students can understand the problem well, have not been able to write a settlement plan correctly, are less able to carry out the steps of the settlement plan, and re-check the answers that have been done.